2003
DOI: 10.1017/s0013091502000809
|View full text |Cite
|
Sign up to set email alerts
|

The Maximal Order Property for Quantum Determinantal Rings

Abstract: We develop a method of reducing the size of quantum minors in the algebra of quantum matrices Oq(Mn). We use the method to show that the quantum determinantal factor rings of Oq(Mn(C)) are maximal orders, for q an element of C transcendental over Q.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…These relations agree with the relations used in [3], [5], [6], [10] and [11], but they differ from those of [12] by an interchange of q and q −1 . It is well known that the ring R is a Noetherian domain.…”
Section: H-invariant Prime Ideals In O Q (M Mp (C))supporting
confidence: 83%
See 2 more Smart Citations
“…These relations agree with the relations used in [3], [5], [6], [10] and [11], but they differ from those of [12] by an interchange of q and q −1 . It is well known that the ring R is a Noetherian domain.…”
Section: H-invariant Prime Ideals In O Q (M Mp (C))supporting
confidence: 83%
“…Using this new tool, we can prove that, if u 3, the ideal in O q (M m,p (C)) generated by Y 1,p and the u × u quantum minors is prime. This result allows Lenagan and Rigal [11] to show that the quantum determinantal factor rings of O q (M m,p (C)) are maximal orders.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Hence, as a consequence of our results, we are able to show that quantum determinantal rings are maximal orders in their division ring of fractions. This generalises results obtained in [9] where it was shown that quantum determinantal rings are maximal orders under the restrictive hypotheses that k is the field of complex numbers and the deformation parameter q is transcendental over ‫.ޑ‬…”
supporting
confidence: 86%
“…The algebras that we study are noncommutative analogues of coordinate rings of natural varieties arising from Lie theory and we want to study them as such. This was already the point of view in the works [6,7] and [8], where properties of geometric nature of related algebras, expressible either in ring theoretic language (integrity, normality), or homologically (AS-Cohen-Macaulay, AS-Gorenstein properties) were studied.…”
mentioning
confidence: 97%